Rebranding Perpustakaan Umum Kota Pasuruan Dalam Upaya Peningkatan Citra Event Story Telling - Indra Gunawan; Pujiyanto Pujiyanto; Fariza Wahyu Arizal (MAVIS : Jurnal Desain Komunikasi Visual, 2019)
Pasuruan City Public Library has an activity that aims to appreciate the talent of elementary school age children in the field of literature through story telling events. The activity is an annual routine activity organized by the public library of Pasuruan city as an effort to get closer to the community. The use of promotional media in story telling events organized by the Pasuruan city public library is needed to attract the attention of the wider community. Considering the lack of media promotion carried out by the Pasuruan city public library, the event lacked support for the community. The design used to promote story telling events in the form of rebranding promotional media and the addition of supporting media in the form of stationary sets and merchandise. Promotional media rebranding is one of the solutions to help increase the attractiveness of the community towards organizing story telling events. The addition of media such as stationary sets and merchandise is not only used to attract the attention of the public, but the use of the media is intended as an added value needed so that the event has a separate identity.